Kuiper Belt object 2014MU69, Pluto and Phoebe as windows on the composition of the early solar nebula. Issue Volume 15:Issue S350(2019) (April 2019) - Pendleton, Y. J.; Cruikshank, D. P.; Stern, S. A.; Dalle Ore, C. M.; Grundy, W.; Materese, C.; Protopapa, S.; Schmitt, B.; Lisse, C.
Abstract: The initial chemical composition of a proto-planetary nebula depends upon the degree to which 1) organic and ice components form on dust grains, 2) organic and molecular species form in the gas phase, 3) organics and ices are exchanged between the gas and solid state, and 4) the precursor and newly formed (more complex) materials survive and are modified in the developing planetary system. Infrared and radio observations of star-forming regions reveal that complex chemistry occurs on icy grains, often before stars even form. Additional processing, through the proto-planetary disk (PPD) further modifies most, but not all, of the initial materials. In fact, the modern Solar System still carries a fraction of its interstellar inheritance (Alexander et al. 2017 ). Here we focus on three examples of small bodies in our Solar System, each containing chemical and dynamical clues to its origin and evolution: the small-cold classical Kuiper Belt object (KBO) 2014 MU 69, Pluto, and Saturn's moon, Phoebe. The New Horizons flyby of 2014 MU 69 has given the first view of an unaltered body composed of material originally in the solar nebula at 45 AU. The spectrum of MU 69 reveals methanol ice (not commonly found), a possible detection of water ice, and the noteworthy absence of methane ice (Stern et al . 2019). Pluto's internal and surface inventory of volatiles and complex organics, together with active geological processes including cryo-volcanism, indicate a surprising level of activity on a body in the outermost region of the Solar System, and the fluid that emerges from subsurface reservoirs may contain material inherited from the solar nebula (Cruikshank et al. 2019 a, b). Meanwhile, Saturn's captured moon, Phoebe, carries high D/H in H2O (Clark et al . 2019 ) and complex organics (Cruikshank et al . 2008 ), both consistent with its formation in, and inheritance from, the outer region of the solar nebula. Together, these objects provide windows on the origin and evolution of our Solar System and constraints to be considered in future chemical and physical models of PPDs.